Pendampingan Implementasi Model Cooperative Learning Tipe Student Teams Achievement Divisions (STAD) Berbasis Difusi Inovasi pada Pembelajaran Fikih di MI Tarbiyatul Wathan - Saiful Bahri (AlMurtado Journal of Social Innovation and Community Service, 2026)
This community service program assisted teachers in implementing Student Teams Achievement Divisions (STAD) in Fikih lessons on halal food at MI Tarbiyatul Wathan, Kraksaan, Probolinggo. The program addressed the need for a structured cooperative model that could expand student participation while strengthening teachers’ understanding of its syntax. Participatory Action Research was employed through needs identification, planning, action, observation, and reflection, while diffusion-of-innovations attributes guided the introduction and adaptation of STAD. The activity was conducted on 15 July 2026 and involved 10 teachers and 22 students from grades V and VI. Qualitative observations indicated that students participated more actively in group discussions and teachers were able to explain the STAD sequence more clearly after the mentoring session. Because no pretest or posttest was administered, the results represent observed process changes rather than statistically measured learning gains. Continued classroom trials and simple assessment instruments are recommended.